Новизна концепції чинної Конституції України - Рудик, Петро Андрійович (My University, 2006)
У статті через призму європейських стандартів та нових підходів до визначення змісту майбутньої Конституції України висвітлюється новизна концепції чинного Основного Закону держави. Україна подається як суверенна національна держава з повновладдям її народу, як президентська республіка з унітарною формою державного устрою, де людина визнається найвищою соціальною цінністю із забезпеченням її прав і свобод. Концепція Конституції закріплювала нові принципи територіального устрою України, організації і здійснення державної влади в Україні на основі верховенства права, поділу влади, заснування поста президента, створення нової виконавчої влади знизу до верху. По-новому постали питання національної безпеки (нейтралітет і без’ядерний статус України), охорони Конституції та конституційного контролю, внесення змін до Основного Закону держави. Водночас зазначаються і недоліки концепції: вона не була позбавлена положень, властивих для часів соціалізму. The article highlighted the novelty of the concept of the current Constitution of the state in the light of European standards and new approaches to determining the content of the future constitution of Ukraine. Ukraine is affirmed as a sovereign nation-state with the sovereignty of the people as a presidential republic with a unitary form of government where the person is recognized as the highest social value of ensuring their rights and freedoms. The concept of the Constitution enshrines the principles of the new territorial structure of Ukraine, the organization and execution of state power in Ukraine based on the rule of law, distribution of powers, founding the president all authorits, create a new executive branch modeled as a vertied. The problems of national security (neutrality and non-nuclear status of Ukraine), the Constitution and the protection of constitutional review, amendments to the Constitution of the State were . At the same time indicated and disadvantages of the concept: it is deprived of provisions peculiar to the times of socialism.
Keywords: Україна; концепція; конституція; Ukraine; concept; Constitution; кафедра економіки і права